Persistent pollution -- past, present and future school of environmental research - organized by Helmholtz-Zentrum Geesthacht - Floser, Gotz; Quante, Markus (Springer, 2011)
This book evolved from the 5th School of Environmental Research entitled Persistent Pollution Past, Present and Future?, which has set a focus on Persistent Organic Pollutants (POPs), heavy metals and aerosols. Research topics covered by the School included the reconstruction of past changes based on the scientific analysis of natural archives such as ice cores and peat deposits, evaluation of the present environmental state by the integration of measurements and modelling and the establishment of cause-effect-patterns, assessment of possible environmental future scenarios including emission and climate change perspectives. Leading scientists in the field of Marine and Atmospheric Chemistry, Meteorology and Modelling, Environmental Chemistry and Physics, as well as Environmental Policy and Management have prepared manuscripts. The book consists of 19 contributions prepared by more than 40 authors. The structure of the book has been outlined according to the topics addressed by the School and includes synthesis chapters which look into the history and reconstruction of environmental pollution, address emission questions, provide a closer look on selected persistent pollutants, deal with transport and modelling aspects, shed light on some health issues related to persistent pollutants, and discuss emerging contaminants in the atmospheric and marine environment.